Beyond geopower: earthly and anthropic geopolitics in The Great Game by War Boutique. (October 2016) - Ingram, Alan; Forsyth, Isla; Gauld, Nicola
This article reconsiders the nature of art and geopolitics and their interrelations via a discussion of The Great Game, an artwork by War Boutique dealing with successive British military interventions in Afghanistan. As we discuss, The Great Game is richly suggestive in terms of the earthly materials and forces at work in geopolitics, or geopower. The main goal of our discussion, however, is to show how pursuing such concerns leads us back towards a consideration of the anthropic and thus beyond geopower. We argue that framing art and geopolitics in terms of the earthly, the affective and the inhuman is suggestive but underplays much of what art is otherwise taken to be, sometimes even within accounts framed in earthly terms. To develop this argument, we first provide an extended discussion of the The Great Game, in which we consider its entanglement of earthly and anthropic dimensions of geopolitics. We then bring this discussion to bear on work that rethinks geopolitics and art through geopower to highlight the continuing need to contend with the anthropic. Third, we discuss how our understanding of art and geopolitics is enhanced by reflection on what makes artistic engagements with geopolitics artistic, considering how The Great Game has moved through a series of artworlds. In conclusion, we underscore the extent to which art is suggestive as an onto-epistemological form of inquiry into geopolitics as well as an aesthetic–political practice with regard to it and reflect on some of the wider stakes of the discussion.